Achieving smoking abstinence is associated with decreased cocaine use in cocaine-dependent patients receiving smoking-cessation treatment - Winhusen, Theresa M. (2013)
BACKGROUND: Past research suggests that a significant relationship exists between cigarette smoking and illicit-stimulant abuse. The present study evaluated the association between achieving smoking abstinence in response to smoking-cessation treatment (SCT) and illicit-stimulant abstinence in cocaine- and/or methamphetamine-dependent participants. METHODS: Secondary analysis of a randomized, 10-week trial conducted at 12 substance use disorder (SUD) treatment programs. Two hundred and sixty seven adults, meeting DSM-IV-TR criteria for cocaine and/or methamphetamine-dependence and interested in quitting smoking were randomized to SUD treatment as usual plus SCT consisting of weekly individual smoking cessation counseling, extended-release (XL) bupropion (300 mg/day), nicotine inhaler, and contingency management for smoking abstinence. Illicit-stimulant-abstinence was measured by self-report and urine drug screens. Smoking abstinence was assessed via self-report and carbon monoxide levels. RESULTS: A significant effect was found for the cocaine-dependent subsample (N=147) in which participants who stopped smoking were abstinent for illicit stimulants an average of 78.2% of the post-smoking-quit weeks (weeks 4-10) relative to 63.6% in participants who continued smoking (X(2)(1)=8.55, p<.01, d=0.36). No significant effects were found for the sample as a whole (N=249) or for the methamphetamine-dependent subsample (N=102). CONCLUSIONS: The present results suggest that cocaine-dependent patients achieving smoking abstinence in response to SCT might evidence not only improved smoking outcomes but improved cocaine-use outcomes as well. Future research to replicate this finding appears warranted.